Prevalence of job stress among non-academic staff of International Islamic University Malaysia (IIUM) Kuantan campus - Phyu, Htike Myat (2014)
Objective: Job stress is one of the most important health issues concerning globally and locally. Job stress affects both physical and mental wellbeing and also effects to work output. The aim of this study was to measure prevalence of job stress among non-academic staff of International Islamic University Malaysia, Kuantan Campus. Methods: Cross sectional study design was used with sample size of 222 non-academic staffs. Participants were identified through multistage stratified random sampling and face-to-face interviewed by using validated self-administered questionnaire that includes background characteristics such as age, gender, smoking, occupational level and marital status; and job using stress identified Job Content Questionnaire (JCQ) in bilingual version. Univariate analyses were conducted using the prevalence and 95% CI. Results: Prevalence of job stress among IIUM Kuantan Campus’ non-academic staffs was 18.5% (95% CI: 13.8-24.0). The mean age for job stress was 32.5 (7.9) years old. Prevalence of job stress was found higher in female (20.7%), non-smoker (19.0%) and those who are single (19.7%). As for occupational level, respondents who were categorized under Grade C have the highest prevalence of job stress which was 20.0%. Conclusion: Prevalence of job stress among IIUM non-academic staffs was lower compared to other studies in Malaysia.